Unconventional Pd@Sulfonated Silica Monoliths Catalysts for Selective Partial Hydrogenation Reactions under Continuous Flow. Issue 16 (20th July 2017) - Liguori, Francesca; Barbaro, Pierluigi; Said, Bilel; Galarneau, Anne; Santo, Vladimiro Dal; Passaglia, Elisa; Feis, Alessandro
Abstract: Doubly functionalized, hierarchical‐porosity silica monoliths were synthesized by postgrafting of sulfonic groups and in situ growth of Pd nanoparticles in that order. PdNP of 3.1 nm size located in the mesopores of the material showed to be evenly distributed within 4.6 % wt Pd monoliths. The system was explored in the continuous‐flow, catalytic partial hydrogenation reaction of 3‐halogeno‐nitrobenzenes and 3‐hexyn‐1‐ol in the liquid phase, showing remarkable conversion, selectivity, and resistance under very mild conditions. Abstract : Unconventionality as a principle : Doubly functionalized, hierarchical‐porosity silica monoliths, synthesized by postgrafting of sulfonic groups and in situ growth of Pd nanoparticles, show remarkable versatility and efficiency as catalysts under very mild conditions in the continuous‐flow, partial hydrogenation reaction of various substrates.